Separator membrane, electrochemical device and electronic device

By using ceramic particles and polymer coatings in the lithium-ion battery isolation film and combining solid electrolyte materials, the short circuit and explosion problems caused by thermal shrinkage of the isolation film at high temperatures are solved, and the heat box of the electrochemical device is improved Test pass rate and high temperature overcharge safety performance.

CN117895188BActive Publication Date: 2025-01-07NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410276832.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2025-01-07
Estimated Expiration
2044-03-12

AI Technical Summary

Technical Problem

The safety problems of short circuits and explosion accidents caused by thermal shrinkage or crushing of the isolation film under high temperature conditions are difficult to effectively solve by the existing technology.

Method used

Design an isolation film, including a base film and an inorganic coating, the coating contains ceramic particles, the Mohs hardness of the ceramic particles is 3~9.5, and the air resistance change rate is ≤30% under high temperature and high pressure conditions, and the The polymer coating is added to the ceramic coating. The polymer particles have different melting points and spherical ranges, and the dynamic friction coefficient is between 0.1 and 0.28. Combined with solid electrolytes such as Li7La3Zr2O12 and alumina, the thermal box test pass rate of the electrochemical device and Overcharge safety performance.

Benefits of technology

Reduce the difference in ion migration rate under high temperature conditions, reduce side reaction generation, improve the gas resistance and puncture strength of the isolation membrane, improve the pass rate of the hot box test and high-temperature overcharge safety performance of the electrochemical device, and extend the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses an isolation membrane, an electrochemical device, and an electronic device, wherein the isolation membrane comprises a base membrane and an inorganic coating disposed on at least one side of the base membrane, wherein the inorganic coating contains ceramic particles, wherein the Mohs hardness of the ceramic particles is 3 to 9.5, and the air resistance change rate of the isolation membrane after heating and compression for 10 minutes at a temperature of 100°C and a pressure of 3.5MPa is ≤30%. The isolation membrane provided by the present application is configured in an electrochemical device to improve the thermal safety performance of the electrochemical device and enhance its overcharge safety performance at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to an isolation membrane, an electrochemical device, and an electronic device. Background Art

[0002] The safety issues caused by lithium-ion batteries under high temperature conditions have continued to attract public attention in recent years. During the charging process, the thermal shrinkage or breakage of the isolation membrane in the lithium-ion battery may cause a short circuit, and more seriously, it may cause an explosion. Therefore, research on the thermal and safety performance of lithium-ion batteries has also attracted more and more attention. Summary of the invention

[0003] In view of this, the present application provides an isolation membrane, an electrochemical device, and an electronic device to improve the thermal performance and safety performance of lithium-ion batteries.

[0004] In the first aspect, the present application provides a separator, the separator comprising a base film and an inorganic coating disposed on at least one side of the base film, the inorganic coating containing ceramic particles, the Mohs hardness of the ceramic particles being 3 to 9.5, and the gas resistance change rate of the separator after heating and compressing for 10 minutes at a temperature of 100°C and a pressure of 3.5MPa is ≤30%. The separator meeting the above conditions is conducive to reducing the significant difference in the local ion migration rate caused by gas obstruction under high temperature and high pressure conditions, and can also reduce the generation of more side reactions caused by product accumulation caused by electrolyte decomposition. At the same time, the separator described in the present application can also maintain a certain gas resistance, that is, under high temperature conditions (above 130°C), the reaction between the positive electrode and the negative electrode can be reduced in time, thereby improving the pass rate of the hot box test of the electrochemical device, and improving the overcharge safety performance of the electrochemical device and the electronic device at high temperature. Preferably, the gas resistance change rate of the separator after heating and compressing for 10 minutes at a temperature of 100°C and a pressure of 3.5MPa is ≤18%.

[0005] In some embodiments, the Mohs hardness of the ceramic particles is 6 to 9.5, and the D50 particle size of the ceramic particles is 50 nm to 400 nm. By adjusting the Mohs hardness of the ceramic particles and the D50 particle size of the ceramic particles within the above range, the pass rate of the hot box test of the electrochemical device can be further improved, and the overcharge safety performance of the electrochemical device and the electronic device at high temperature can be improved.

[0006] In some embodiments, the isolation membrane further includes a polymer coating, the polymer coating is disposed on the inorganic coating, the polymer coating contains first polymer particles and second polymer particles, the melting point of the first polymer particles is 65°C to 100°C, and the melting point of the second polymer particles is 135°C to 160°C. The inventors speculate that when the polymer coating has the above two substances with different melting points, the polymer can exert appropriate adhesion under different temperature conditions, so that the isolation membrane maintains a suitable puncture strength, and improves the floating capacity retention rate of the assembled electrochemical device, and reduces the floating capacity expansion rate of the electrochemical device.

[0007] In some embodiments, the sphericity of the first polymer particles is X, 0.7≤X≤0.95, and the sphericity of the second polymer particles is Y, 0≤(XY)≤0.2. The inventor unexpectedly discovered that when the polymer coating has the above two polymers with melting points and the two polymer particles meet the sphericity range of the present application, it is beneficial for the polymers to timely exert appropriate bonding at temperatures under different operating conditions, so that the isolation membrane maintains appropriate puncture strength, improves the floating capacity retention rate of the assembled electrochemical device, and reduces the floating capacity expansion rate of the electrochemical device.

[0008] In some embodiments, the dynamic friction coefficient of the separator is 0.1 to 0.28. When the dynamic friction coefficient of the separator surface meets this range, the separator is less likely to move relative to the positive and negative electrodes during winding, thereby reducing the risk of short circuit caused by the contact between the positive and negative electrodes due to the sliding of the separator; when the friction coefficient is within this range, the appropriate layer gap can be increased to improve the puncture resistance of the separator, while reducing the possibility of burrs piercing the separator due to the sliding of the separator, thereby reducing the risk of short circuit of the electrochemical device, improving the pass rate of the hot box test of the electrochemical device, and improving the overcharge safety performance of the electrochemical device and electronic equipment at high temperature. When the dynamic friction coefficient is too large or too small, it will affect the wetting effect of the electrolyte, thereby deteriorating the charge and discharge performance of the electrochemical device or electronic device, reducing the floating capacity retention rate of the electrochemical device, and increasing the floating capacity expansion rate of the electrochemical device.

[0009] In some embodiments, the Dv50 of the first polymer is in the range of 1 to 1.8 μm, and the Dv50 of the second polymer is in the range of 1.2 to 2.3 μm. When the Dv50 of the first polymer and the second polymer meet the range of this application, the two polymers will show a suitable viscosity, which is conducive to the timely and appropriate bonding of the polymers under different operating conditions, so that the isolation membrane maintains a suitable puncture strength, and improves the floating capacity retention rate of the assembled electrochemical device, and reduces the floating capacity expansion rate of the electrochemical device.

[0010] Second aspect, the present application provides an electrochemical device, which includes a solid electrolyte and the separator membrane described in any one of the above.

[0011] In some embodiments, the solid electrolyte includes an organic solid electrolyte and an inorganic substance. The organic solid electrolyte is selected from solid polymer electrolytes containing polyethylene oxide (PEO), polypropylene oxide (PPO), polyethyleneimine (PEI), polyethylene sulfide (PES), and polyvinyl acetate (PVAc). The inorganic substance is selected from Li7La3Zr2O 12 (LLZO), aluminum oxide (Al2O3), silicon dioxide (SiO2), Li 3x1 La 2 / 3-x1 TiO3 (LLTO), Li 1+x2 Al x2 Ti 2-X2 (PO4)3 (LATP), Li 1+x3 Al x3 Ge 2-X3 (PO4)3 (LAGP), Li 1.4 Zn(GeO4)4, Li3N, Li 3+y PO 4-x4 N x4 (LIPON), Li 3.6 Si 0.6 P 0.4 O4 or a combination thereof, where 0 < x1 < 1, 0 < x2 < 1, 0 < x3 < 1, 0 < x4 < 4, 0 < y < 3. Alternatively, the organic solid electrolyte is selected from gel polymer electrolytes containing polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride - hexafluoropropylene copolymer (PVDF - HFP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), and polyvinyl acetate (PVAc). The solid electrolyte that meets the above range of the present application is beneficial to improving the voltage use window of the electrochemical device. By using an inorganic substance of a fast ion conductor material and combining it with a polymer having excellent film - forming properties and ductility, the long - cycle performance at high and low temperatures can be improved.

[0012] In some embodiments, the solid electrolyte includes polyethylene oxide and Li7La3Zr2O 12 , and the mass ratio of polyethylene oxide to Li7La3Zr2O 12 is (1:3) ~ (3:1). By selecting a suitable inorganic substance with fast ion conduction and combining it with a polymer having excellent film - forming properties and ductility, and making the two meet the range of the present application, the long - cycle performance at high and low temperatures can be improved.

[0013] In some embodiments, the solid electrolyte includes at least polyethylene oxide, Al2O3 and Li7La3Zr2O 12 At least one of the three, preferably, when all three substances are included, polyethylene oxide, Al2O3 and Li7La3Zr2O 12 The mass ratio of is (1-3):1:(1-3). By adding alumina and selecting a suitable inorganic substance with fast ion conduction and a polymer with excellent film-forming properties and ductility, so that the three meet the range of this application, the hardness and strength of the isolation membrane can be improved, and the long cycle performance of the electrochemical device at high and low temperatures can be improved.

[0014] In some embodiments, the electrochemical device has a highest oxidation peak in a voltage window range of 4V to 5V in a linear cyclic voltammetry test, wherein the scanning voltage range is 3V to 6V and the scanning rate is 0.5mV / s.

[0015] In a third aspect, the present application provides an electronic device, comprising any one of the electrochemical devices described above.

[0016] The beneficial effects brought about by the technical solutions provided by some embodiments of the present application include at least:

[0017] The isolation membrane provided in the first aspect of the present application has a suitable gas resistance change rate before and after certain high temperature and high pressure conditions, and ceramic particles with a suitable Mohs hardness are selected in the inorganic coating, which reduces the phenomenon of significant local differences in ion migration rate caused by gas obstruction. At the same time, the isolation membrane of the present application can further reduce the generation of more side reactions due to the accumulation of electrolyte decomposition products. At the same time, under high temperature conditions (above 130°C), it can timely reduce the reaction between the positive and negative electrodes, thereby improving the hot box test pass rate of the electrochemical device, and improving the overcharging safety performance of the electrochemical device provided in the second aspect of the present application and the electronic device provided in the third aspect at high temperature. DETAILED DESCRIPTION

[0018] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0019] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0020] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0021] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0022] Isolation film

[0023] In a first aspect, an embodiment of the present application provides an isolation film, the isolation film comprising a base film and an inorganic coating disposed on at least one side of the base film, the inorganic coating containing ceramic particles, the Mohs hardness of the ceramic particles being 3 to 9.5, and the air resistance change rate of the isolation film after heating and compressing at a temperature of 100°C and a pressure of 3.5MPa for 10 minutes is ≤30%. Preferably, the air resistance change rate of the isolation film after heating and compressing at a temperature of 100°C and a pressure of 3.5MPa for 10 minutes is ≤18%. Exemplarily, the Mohs hardness of the ceramic particles is 3, 4, 5, 6, 7, 8, 9, 9.5 or a range consisting of any two of the above values.

[0024] In some embodiments, the D50 particle size of the ceramic particles is 50 nm to 400 nm. Exemplarily, the D50 particle size of the ceramic particles is 50 nm, 60 nm, 80 nm, 120 nm, 150 nm, 180 nm, 200 nm, 250 nm, 280 nm, 300 nm, 350 nm, 400 nm, or a range consisting of any two of the above values.

[0025] In some embodiments, the isolation film further includes a polymer coating, which is disposed on the inorganic coating, and the polymer coating contains first polymer particles and second polymer particles, the melting point of the first polymer particles is 65°C to 100°C, and the melting point of the second polymer particles is 135°C to 160°C. Exemplarily, the melting point of the first polymer particles is 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or a range consisting of any two of the above values. Exemplarily, the melting point of the second polymer particles is 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, or a range consisting of any two of the above values.

[0026] In some embodiments, the sphericity of the first polymer particles is X, 0.7≤X≤0.95, and the sphericity of the second polymer particles is Y, 0≤(XY)≤0.2. Exemplarily, the sphericity X of the first polymer particles is 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or a range consisting of any two of the above values. Exemplarily, the value of (XY) is 0, 0.001, 0.01, 0.05, 0.1, 0.15, 0.2, or a range consisting of any two of the above values.

[0027] In some embodiments, the Dv50 range of the first polymer is 1 to 1.8 μm, and the Dv50 range of the second polymer is 1.2 to 2.3 μm. Exemplarily, the Dv50 of the first polymer particles is 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, or a range consisting of any two of the above values. The Dv50 of the second polymer particles is 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, or a range consisting of any two of the above values. The Dv50 in this application represents the particle size that reaches 50% of the cumulative volume from the small particle size side in the particle size distribution based on volume.

[0028] Electrochemical Devices

[0029] The electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator and a solid electrolyte.

[0030] The isolation film is the isolation film mentioned above.

[0031] The solid electrolyte comprises an organic solid electrolyte and an inorganic substance, wherein the organic solid electrolyte is selected from a solid polymer electrolyte containing polyethylene oxide, polypropylene oxide, polyethylene imine, polyethylene sulfide and polyvinyl acetate; or, the organic solid electrolyte is selected from a gel polymer electrolyte containing polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile and polyvinyl acetate; and the inorganic substance is selected from Li7La3Zr2O 12 、Al2O3、SiO2、Li 3x1 La 2 / 3-x1 TiO3、Li 1+x2 Al x2 Ti 2-X2 (PO4)3、Li 1+x3 Al x3 Ge 2-X3 (PO4)3、Li 1.4Zn(GeO4)4, Li3N, Li 3+y PO 4-x4 N x4 , Li 3.6 Si 0.6 P 0.4 O4 or a combination thereof, wherein 0 <x1<1,0<x2<1,0<x3<1,0<x4<4,0<y<3。

[0032] In some embodiments, the solid electrolyte comprises polyethylene oxide and Li7La3Zr2O 12 , polyethylene oxide and Li7La3Zr2O 12 The mass ratio is (1:3)~(3:1).

[0033] In some embodiments, the solid electrolyte includes polyethylene oxide, Al2O3 and Li7La3Zr2O 12 , polyethylene oxide, Al2O3 and Li7La3Zr2O 12 The mass ratio is (1~3):1:(1~3).

[0034] The negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0035] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0036] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80~99): (0.5~10): (0.5~10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0037] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer may be located on one side or both sides of the positive current collector. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of ​​the positive current collector. In some embodiments, the thickness of the positive active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only, and other suitable thicknesses may be used.

[0038] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the positive electrode active material may be doped and / or coated.

[0039] In some embodiments, the surface of the positive electrode material includes lithium phosphate and / or lithium niobate, the mass ratio of the two is 1:5-1:1, and the thickness of the covering layer is 1-2 μm.

[0040] In some embodiments, the positive electrode active material layer also includes a positive electrode binder and a positive electrode conductor. In some embodiments, the positive electrode binder may include polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the positive electrode conductor may include at least one of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes or carbon fibers.

[0041] The electrochemical device can be prepared according to conventional methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain an electrode assembly, or the electrode assembly can be obtained by winding; the electrode assembly is placed in a packaging shell, and the electrolyte is injected and sealed to obtain the electrochemical device.

[0042] The electrochemical device of the present application may include any device that generates an electrochemical reaction. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0043] Electronic devices

[0044] The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0045] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0046] Example

[0047] Exemplary preparation method of inorganic coating: Ceramic particles with a volume average particle size Dv50 of 50nm to 400nm and binder polyacrylate are dispersed in deionized water at a mass ratio of 90:10 to form an inorganic coating slurry with a solid content of 45% to 50%, and the inorganic coating slurry is uniformly coated on one side of a PE porous substrate with a thickness of 8μm to 10μm by a micro-concave coating method, and the inorganic coating is obtained after drying in an oven. The thickness of the inorganic coating is 2 to 4μm.

[0048] An exemplary preparation method of a polymer coating is as follows: first polymer particles and second polymer particles are added to a stirrer and stirred evenly; sodium carboxymethyl cellulose is added to a stirrer and stirred evenly; dimethylsiloxane, a wetting agent, is added to a stirrer, and then deionized water is added and stirred to adjust the viscosity of the slurry to 40 mPa•s ~45mPa•s and the solid content to 5%~8% of the first coating slurry. The first coating slurry is evenly coated on the inorganic coating and dried in an oven to obtain a first coating. The thickness of the first coating is 2~4μm.

[0049] Example 1-1

[0050] <Preparation of lithium-ion batteries>

[0051] Preparation of positive electrode

[0052] Lithium iron phosphate, positive electrode conductive agent acetylene black, and positive electrode binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 85:7:8 and added to N-methylpyrrolidone, stirred, and prepared into a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85℃ to obtain a positive electrode sheet coated with a positive electrode mixture layer on one side, and the above steps were repeated on the other side of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, it was dried at 85℃ under vacuum conditions for 4 hours to obtain a positive electrode sheet with a specification of 74mm×867mm.

[0053] Preparation of negative electrode

[0054] Weigh 100g of negative electrode active material (artificial graphite with a particle size of 12μm), 1g of conductive agent (carbon black), and 4g of binder (styrene-butadiene rubber, SBR) and add them to 2.8g of N-methylpyrrolidone and 108g of water to form a negative electrode slurry with a solid content of 75wt%. The negative electrode slurry is evenly coated on one side of a 13μm negative electrode collector copper foil, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 85μm on one side. Repeat the above steps on the other side of the negative electrode collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 76mm×851mm is obtained.

[0055] Preparation of solid electrolyte

[0056] In a glove box filled with argon, PEO matrix and LLZO powder in a mass ratio of 1:4 and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a molar ratio of lithium salt to PEO of 1:12 were weighed and stirred into a uniform solution at room temperature. The uniform solution was quantitatively poured into a polytetrafluoroethylene mold and dried in an argon atmosphere at 60°C to obtain a solid electrolyte.

[0057] Preparation of isolation membrane

[0058] A polyethylene (PE) microporous membrane with a thickness of 8 μm was selected as the base membrane.

[0059] Preparation of inorganic coating: Boehmite (ceramic particles) with a volume average particle size Dv50 of 50 nm and binder polyacrylate were dispersed in deionized water at a mass ratio of 90:10 to form an inorganic coating slurry with a solid content of 45%. The inorganic coating slurry was evenly coated on one side of a PE porous substrate with a thickness of 8 μm by a micro-concave coating method, and dried in an oven to obtain a separator containing an inorganic coating. The thickness of the inorganic coating was 2 μm.

[0060] Preparation of lithium-ion batteries

[0061] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no particular restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the composite electrolyte membrane and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or, stacking the positive electrode sheet, the composite electrolyte membrane and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging. Among them, the packaging bag is a packaging bag known in the art, and the present application does not limit this.

[0062] <Lithium-ion battery performance test>

[0063] (1) Low temperature (-15°C) performance test:

[0064] The lithium ion batteries of the embodiments and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention rate of the lithium ion batteries was calculated.

[0065] In an environment of -15°C, the first charge and discharge were carried out. Constant current charging was carried out at a charging current of 2C to a full charge voltage of 3.8V, and then constant voltage charging was carried out at the maximum voltage until the current was 0.02C, and then constant current discharge was carried out at a discharge current of 0.5C until the final voltage was 2.0V, and the discharge capacity of the first cycle was recorded; then the above steps were repeated for 400 charge and discharge cycles, and the discharge capacity of the 400th cycle was recorded.

[0066] Cycle capacity retention rate = (discharge capacity of the 400th cycle / discharge capacity of the first cycle) × 100%.

[0067] (2) 4.5C 5V 70℃ overcharge test:

[0068] The battery was discharged at 0.5C to 2.0V at 25°C, then charged at a constant current of 3.5C to 5V, and then charged at a constant voltage for 3h, and the surface temperature change of the battery cell was monitored (the passing standard was that the battery cell did not catch fire, burn, or explode). Ten samples were tested for each embodiment.

[0069] (3) Hot box test:

[0070] The lithium-ion batteries in each embodiment and each comparative example were charged at room temperature at a constant current of 0.5C to a full charge voltage of 3.8V, and then continued to be charged at a constant voltage of 3.8V to a cut-off current of 0.05C to make them fully charged, and the appearance was checked to ensure that the lithium-ion batteries were in a normal usable state. The fully charged batteries were placed in an oven, and the temperature was increased at a rate of 5°C / min until the specified hot box test temperature of 140°C was reached, and the temperature was kept constant for one hour. During this process, the battery status was observed, and 5 samples were used for testing in each embodiment.

[0071] Judgment criteria: The battery does not catch fire or explode.

[0072] Hot box test pass rate = number of hot box tests passed / total number.

[0073] (4) 40℃ charge and discharge performance test:

[0074] The lithium ion batteries of the embodiments and comparative examples were repeatedly charged and discharged by the following steps, and the discharge capacity retention rate of the lithium ion batteries was calculated.

[0075] In an environment of 40°C, the first charge and discharge were carried out. Constant current charging was carried out at a charging current of 2C to a full charge voltage of 3.8V, and then constant voltage charging was carried out at the maximum voltage until the current was 0.02C, and then constant current discharge was carried out at a discharge current of 0.5C until the final voltage was 2.0V, and the discharge capacity of the first cycle was recorded; then the above steps were repeated for 500 charge and discharge cycles, and the discharge capacity of the 500th cycle was recorded.

[0076] Cycle capacity retention rate = (discharge capacity at the 500th cycle / discharge capacity at the first cycle) × 100%.

[0077] (5) Air resistance test

[0078] The separator was fixed between a clamp and an adapter plate without wrinkles using a Gurley air permeability tester type B manufactured by Tester Industry Co., Ltd., and the measurement was carried out according to the JIS P8117 method. 2 The measurement points are the center and four corners of the sample, a total of 5 points, and the average value is used as the air resistance. In addition, when the length of one side of the sample is less than 10cm, the value measured at 5 points at 5cm intervals can also be used.

[0079] The increase in air resistance is calculated according to the following formula.

[0080] The increase of air resistance = (A) - (B) sec / 100ccAir;

[0081] Air resistance of the isolation film (B) sec / 100ccAir;

[0082] Air resistance of the diaphragm (A) sec / 100ccAir.

[0083] (6) Floating charge performance test

[0084] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it at a constant current of 1C until the voltage is 3.8V, charge it at a constant voltage until the current is 0.05C, and then discharge it at a constant current of 1C until the voltage is 2.0V. Record the discharge capacity as the initial capacity of the lithium-ion battery.

[0085] Then charge at a constant current of 0.5C to a voltage of 3.8V, charge at a constant voltage to a current of 0.05C, and use a micrometer to test and record the thickness of the battery as the initial thickness. Transfer the test lithium-ion battery to a 45°C constant temperature box, and then charge at a constant voltage of 3.8V for 60 days. After 60 days, transfer the battery to a 25°C constant temperature box, let it stand for 60 minutes, and discharge at a constant current of 1C to a voltage of 2.0V. Record the discharge capacity as the discharge capacity of the lithium-ion battery after storage;

[0086] Then charge with 1C constant current to the voltage of 3.8V, charge with constant voltage to the current of 0.05C, and then discharge with 1C constant current to 2.0V. Record the discharge capacity as the recoverable capacity of the lithium-ion battery, and measure the thickness of the lithium-ion battery as the thickness after floating charge.

[0087] Float charge thickness expansion rate = (thickness after float charge - initial thickness) / initial thickness × 100%;

[0088] Floating capacity retention rate = (initial discharge capacity - recoverable capacity) / initial discharge capacity × 100%.

[0089] (7) Isolation film puncture strength test

[0090] The puncture strength was tested according to the requirements of ASTM D4833-00e1, wherein the needle shape was a hemisphere of Ф=1.0 mm, the needle running speed was 1 mm / s, and the average value was taken after five measurements.

[0091] (8) LSV linear cyclic voltammetry test:

[0092] The assembled battery was subjected to electrochemical linear sweep voltage (LSV) testing with a linear sweep potential range of 3 V to 6 V and a scan rate of 0.5 mV / s.

[0093] (9) Dynamic friction coefficient test:

[0094] The dynamic friction coefficient was measured according to the requirements of JIS K7125.

[0095] Except for adjusting the relevant parameters according to Table 1, the other aspects of Examples 1-2 to 1-14 and Comparative Examples 1-1 to 1-7 are the same as those of Example 1-1.

[0096] Compared with Example 1-1, the differences between Example 2-0 to Example 2-28 are:

[0097] In Examples 2-0 to 2-28, a polymer coating is further prepared on the surface of the isolation membrane containing an inorganic coating in Example 1-1. Exemplarily, the preparation method of Example 2-0 is as follows: first polymer particles with a melting point of 65°C (polymer particles based on propylene, Dv50 of 1 μm) and second polymer particles with a melting point of 145°C (polymer particles based on vinylidene fluoride, Dv50 of 1.2 μm) are added to a stirrer and stirred evenly; sodium carboxymethyl cellulose is added to the stirrer and stirred evenly; dimethylsiloxane, a wetting agent, is added to the stirrer, and then deionized water is added and stirred to adjust the viscosity of the slurry to 40 mPa•s and the solid content to 7% to obtain a first coating slurry. The first coating slurry is evenly coated on the inorganic coating, and after drying in an oven, a first coating is obtained. The coating weight of the first coating slurry is 1.2 mg / 5000 mm 2 The thickness of the first coating layer is 2 μm, the mass ratio of the first polymer, the second polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 75:18:2:5, and the sphericity of the first polymer is 0.7. The preparation methods of Examples 2-1 to 2-28 can refer to the preparation method of Example 2-0, and the preparation parameters are shown in Table 2.

[0098] The difference between Example 3-1 to Example 3-25 and Example 1-1 is that, except for adjusting the relevant preparation parameters according to Table 3, the rest are the same as Example 1-1.

[0099] Table 1

[0100]

[0101] Combined with Table 1, by comparing Comparative Examples 1-1 to Comparative Examples 1-2 with Example 1-1, it can be seen that by adding ceramic particles with a suitable particle size and Mohs hardness to the preparation of the electrodeless coating of the isolation membrane, the prepared isolation membrane has an air resistance change rate of ≤30% after heating and compression for 10 minutes at a temperature of 100°C and a pressure of 3.5 MPa, which is beneficial to improving the hot box test pass rate of lithium-ion batteries, and can also improve the overcharge test pass rate of lithium-ion batteries at high temperatures.

[0102] In particular, further adjusting the Mohs hardness and D50 particle size of the ceramic particles can achieve a better effect of improving the pass rate of the hot box test of lithium-ion batteries, and the overcharge safety performance of lithium-ion batteries at high temperatures is also better. However, when the prepared isolation film does not meet the air resistance change range of ≤30% under the temperature, pressure or time specified in this application, it is not conducive to improving the pass rate of the hot box test of lithium-ion batteries, nor is it conducive to improving the pass rate of the overcharge test of lithium-ion batteries at high temperatures.

[0103] Table 2

[0104]

[0105] It can be seen from Table 2 that when the polymer coating has the above-mentioned two substances with different melting points, the floating capacity retention rate of the lithium-ion battery can be improved, and the floating capacity expansion rate of the electrochemical device can be reduced. In particular, when the sphericity of the polymer particles is further limited, the effect of improving the floating performance of the lithium-ion battery is better. When the dynamic friction coefficient of the isolation membrane meets the scope of this application, the isolation membrane can have a suitable and excellent puncture resistance. When the dynamic friction coefficient is too large / too small, the charge and discharge performance of the electrochemical device or electronic device will be deteriorated, the floating capacity retention rate of the electrochemical device or electronic device will be reduced, and the floating capacity expansion rate of the electrochemical device or electronic device will be increased.

[0106] Table 3

[0107]

[0108] From Table 3, it can be seen that when the electrolyte is a solid electrolyte and the solid electrolyte contains the above-mentioned organic solid electrolyte and inorganic substance, it is beneficial to improve the voltage window of the lithium-ion battery, and the ratio of the organic solid electrolyte to the inorganic substance is in a suitable range, which can further improve the voltage window of the lithium-ion battery, so that the electrochemical device can also have excellent cycle performance under high temperature and high voltage usage scenarios.

[0109] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A separation film, characterized in that: The isolation film comprises a base film and an inorganic coating disposed on at least one side of the base film; The inorganic coating contains ceramic particles, the Mohs hardness of the ceramic particles is 3 to 9.5; the D50 particle size of the ceramic particles is 50 nm to 400 nm; the type of the ceramic particles is selected from any one of boehmite, calcium carbonate, fluorite, apatite, silicon dioxide, quartz, zirconium oxide or boron carbide; The air resistance change rate of the isolation film after heating and compressing for 10 minutes at a temperature of 100°C and a pressure of 3.5MPa is ≤30%; The isolation film further includes a polymer coating, which is disposed on the inorganic coating; the polymer coating contains first polymer particles and second polymer particles, the melting point of the first polymer particles is 65° C. to 100° C., and the melting point of the second polymer particles is 135° C. to 160° C.; the sphericity of the first polymer particles is X, 0.7≤X≤0.95; the sphericity of the second polymer particles is Y, 0≤(XY)≤0.2; The dynamic friction coefficient of the isolation film is 0.1-0.

28.

2. The isolation film according to claim 1, characterized in that: At least one of the following conditions is met: (1) The Mohs hardness of the ceramic particles is 6 to 9.5; (2) The air resistance change rate of the isolation film after heating and compressing for 10 minutes at a temperature of 100° C. and a pressure of 3.5 MPa is ≤18%.

3. The isolation film according to claim 1, characterized in that: The Dv50 of the first polymer is in the range of 1 μm to 1.8 μm, and the Dv50 of the second polymer is in the range of 1.2 μm to 2.3 μm.

4. An electrochemical device, characterized in that: The electrochemical device comprises a solid electrolyte and the separator according to any one of claims 1 to 3.

5. The electrochemical device according to claim 4, characterized in that The solid electrolyte includes an organic solid electrolyte and an inorganic substance; The organic solid electrolyte is selected from a solid polymer electrolyte containing polyethylene oxide, polypropylene oxide, polyethylene imine, polyethylene sulfide and polyvinyl acetate; or, The organic solid electrolyte is selected from a gel polymer electrolyte containing polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile and polyvinyl acetate; The inorganic substance is selected from Li7La3Zr2O 12 、Al2O3、SiO2、Li 3x1 La 2 / 3-x1 TiO3、Li 1+x2 Al x2 Ti 2-X2 (PO4)3、Li 1+x3 Al x3 Ge 2-X3 (PO4)3、Li 1.4 Zn(GeO4)4, Li3N, Li 3+y PO 4-x4 N x4 , Li 3.6 Si 0.6 P 0.4 O4 or a combination thereof; Among them, 0 <x1<1,0<x2<1,0<x3<1,0<x4<4,0<y<3。 6. The electrochemical device according to claim 5, characterized in that The solid electrolyte includes polyethylene oxide and Li7La3Zr2O 12 ; Polyethylene oxide and Li7La3Zr2O 12 The mass ratio is (1:3) to (3:1).

7. The electrochemical device according to claim 5, characterized in that The solid electrolyte includes polyethylene oxide, Al2O3 and Li7La3Zr2O 12 At least one of the three.

8. The electrochemical device according to claim 7, characterized in that The polyethylene oxide, the Al2O3 and the Li7La3Zr2O 12 The mass ratio is (1~3):1:(1~3).

9. The electrochemical device according to any one of claims 4 to 8, characterized in that: In a linear cyclic voltammetry test, the electrochemical device has a highest oxidation peak within a voltage window range of 4V to 5V; Among them, the scanning voltage range is 3V~6V, and the scanning rate is 0.5mV / s.

10. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Battery separator and production method therefor

    CN106463679A

  • Polyolefin microporous membrane, separator for cell, and cell

    CN106575734A

  • Layered polyolefin microporous membrane, separator for batteries, and methods for manufacturing same

    CN107431166A

  • Battery diaphragm and preparation method thereof, and lithium battery

    CN109473602A

  • Commercial diaphragm-based sandwich structure polymer composite solid electrolyte membrane and preparation method thereof

    CN112909316A